2018
DOI: 10.1155/2018/8141056
|View full text |Cite
|
Sign up to set email alerts
|

Improving Long-Term Outcomes for Patients with Extra-Abdominal Soft Tissue Sarcoma Regionalization to High-Volume Centers, Improved Compliance with Guidelines or Both?

Abstract: Introduction Optimization of outcomes of extra-abdominal STS is not clearly understood. We sought to determine whether hospital surgical volume and adherence to NCCN guidelines, or both, are associated with outcomes in the treatment of extra-abdominal soft tissue sarcoma (STS). Methods The National Cancer Database (NCDB) was queried for patients undergoing surgery for extra-abdominal STS diagnosed from 2003 to 2007. Mean annual hospital volume for STS surgery was divided into volume terciles (1T ≤3, 2T 4–10, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…We recently reported that presentation to a specialized multidisciplinary tumor board (MDTB) was independently correlated to reduction in the risk of relapse in a nationwide study involving the NETSARC Network [12]. Similar observations were reported by several other national initiatives [13–15].…”
Section: Introductionmentioning
confidence: 53%
“…We recently reported that presentation to a specialized multidisciplinary tumor board (MDTB) was independently correlated to reduction in the risk of relapse in a nationwide study involving the NETSARC Network [12]. Similar observations were reported by several other national initiatives [13–15].…”
Section: Introductionmentioning
confidence: 53%
“…4,5 Although several studies have shown that adherence to guidelines results in better patient outcomes, 32-70% of patients with STS are not consistently treated in accordance with the clinical guidelines. [6][7][8][9][10][11] This study aimed to acquire insight into the variation of eSTS management by assessing the influence of clinical specialty and continent on clinical practice and surveillance. Additionally, this study investigated the extent to which selected patient and disease characteristics are used to distinguish between high-and low-risk patients and the extent to which these factors are used in clinical decision-making for perioperative treatment.…”
mentioning
confidence: 99%
“…Data from other malignancies such as sarcoma have suggested that adherence to NCCN guidelines, irrespective of hospital volume, was associated with improved overall survival for patients with extra-abdominal soft tissue sarcomas. 30 In fact, while in that study high-volume hospitals were more often adherent to guidelines, low-volume hospitals that followed national guidelines had achieved comparable outcomes. Similarly, we noted that irrespective of high-versus low-volume hospital status, there was an increase in the use of multi-modality therapy for high-risk CCA as recommended by NCCN guidelines, which may have contributed to the "across the board" survival improvements noted over time.…”
Section: Discussionmentioning
confidence: 79%